The Influence of Natural Language-Based Chatbot Usage on User Experience in Online Customer Service - Jumriyah, Jumriyah; Nizam, Zain; Idris, Haziq (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The rapid development of artificial intelligence has led to an increased use of natural language-based chatbots in various industries, particularly in online customer service. These chatbots have become essential tools for improving customer engagement, providing timely support, and enhancing the overall user experience. However, despite their growing popularity, the impact of chatbot usage on user experience in online customer service remains underexplored. This study investigates the influence of natural language-based chatbot usage on user experience in online customer service settings. The research aims to evaluate how chatbot interactions affect customer satisfaction, ease of use, and perceived efficiency in addressing customer queries. A mixed-methods approach was employed, utilizing quantitative surveys and qualitative interviews with users who interacted with a natural language-based chatbot on an e-commerce platform. The data collected were analyzed to assess the correlation between chatbot usage and user experience. The results revealed that users who interacted with the chatbot reported higher levels of satisfaction and perceived efficiency compared to those who used traditional customer service methods. The ease of use and quick response times contributed to positive user experiences, although some users expressed concerns about the chatbot’s ability to handle complex queries. The study concludes that natural language-based chatbots can significantly improve user experience in online customer service, but further improvements are needed to enhance their capabilities in addressing more complex issues.